Trust Model for Peer-To-Peer Systems - S Borade, Dipti; Gulwe, Kalpana S; Chaudhari, Ganesh R; Aghav, Satish N; Ahire, Mayur A (International Journal of Computer Sciences and Engineering, 2015)
In networked system, peer-to-peer systems are widely used in today’s world. Widely growing networks and openness of networked systems brings some sort of insecurities in the interactions and operations. Hence, in this paper, we make a trust network first. In this trust network model, we make some trust relationships between systems or peers which are going to interact. So that, this helps peers to make decisions whether to interact with particular peer or system or not.